A Global hydrological index describes ecological conditions in rivers: A new approach to environmental flow calculation reflecting macroinvertebrate requirements - Andrzej Wałęga; Renata Kędzior; Tomasz Skalski; Dariusz Młyński (Ecological Indicators)
The aim of the study was to develop a new method for estimating e-flow linking hydrological parameters and macroinvertebrate communities as indicators of the ecological status of rivers. Four components of the hydrological cycle were used: monthly flow rate, duration and magnitude of extreme flow conditions, frequency and duration of high and low flow pulses, and changes in the rate and frequency of the hydrological cycle. The Global Index (GI), reflecting crucial elements of hydrological influence on habitat quality and river ecological status, and the multiannual mean flow were used to determine e-flow. The global hydrological regime and the ecological and trophic structure of 1200 local macroinvertebrate communities were analyzed in 30 catchments in Poland. Estimated water deficits in rivers (based on combined e-flow and water resources requirements), we analyzed how the methods used to determine e-flow could affect water management. The analysis highlighted significant variations in water shortages among different catchment groups, with larger water quantities needed to support the survival of macroinvertebrates in catchments with high GI values. In case of smaller catchments, where water resources are limited, lesser quantity of water can be used on people activities and higher water should be guaranteed to achieve properly biodiversity of macroinvertebrates. To implement effective river management, the balance between environmental requirements and human activities needs more attention, emphasizing the quantity, timing, and quality of water required to support freshwater and water-dependent ecosystems along with the needs of human users of water resources.